Perlindungan Hukum Atas Kebocoran Data Dan Informasi Pribadi Pada Penumpang Transportasi Udara - Fitria Dewi Navisa; Angelina Septa Roekmanda Sari; Delfi Yumita Ramadhani (Yurispruden: Jurnal Fakultas Hukum Universitas Islam Malang, 2022)
Air transportation service companies often fail to fulfill their consumer rights, such as being irresponsible for leaking passenger data. In connection with this case, there is a need for legal protection for consumers who feel that they have been harmed. This air transportation service provider has a huge responsibility to maintain the privacy of its passengers and consumers. So that by using a normative juridical research method, the author can take the subject matter raised, namely how is legal protection for air transportation services that are affected by data leaks carried out by irresponsible persons from airline companies. By using the theory of legal protection and legal certainty, the author can conclude that actions related to the spread of a personal matter are unlawful acts, whether intentional or not based on negligence, which can lead to liability such as compensation by the airline.